Know Thy Outgroup: Promoting Accurate Judgments of Political Attitude Differences Through a Conflict Mindset. (November 2015) - Stern, Chadly; Kleiman, Tali
In three studies, we examined whether activating a reasoning process that fosters the consideration of alternatives (a conflict mindset) reduces the extent to which individuals consistently overestimate how different outgroup members' attitudes are from their own attitudes. In Study 1, tacitly activating a conflict mindset reduced the overestimation of outgroup dissimilarity compared to a control condition. Study 2 ruled out the alternative explanation that conflict reduces the tendency to overestimate outgroup dissimilarity through diminishing effortful thought. Study 3 showed that a conflict mindset, but not an accuracy incentive, reduced the tendency to overestimate outgroup dissimilarity. Additionally, Study 3 demonstrated that reductions in perceived self–outgroup distance explained in part why a conflict mindset attenuated the overestimation of outgroup dissimilarity. Implications for social judgment accuracy are discussed.